(untitled) (Canadian Rheumatology Today, 2024)
Inflammatory bowel diseases (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), affect almost 1% of the Canadian population and are characterized by debilitating gastrointestinal (GI) symptoms including chronic diarrhea, rectal bleeding and abdominal pain. Beyond involvement of the GI tract, up to half of patients with IBD will also experience extraintestinal manifestations (EIMs) or be diagnosed with comorbid immune-mediated inflammatory diseases (IMIDs), which are associated with substantial morbidity and impaired quality of life. The most common of these are inflammatory joint diseases, including peripheral and axial spondyloarthritis or concomitant rheumatoid (RA) or psoriatic arthritis (PsA), affecting up to 1 in 5 patients with IBD.